Edukasi Penggunaan E-Filing Melalui Program Relawan Pajak Di Kantor Pelayanan Pajak Pratama Jepara - Warno Warno; Nina Nuraina; Adibatur Rahmawati; Nanda Rizka Amalia; Riza Muizzah Asri; Elisa Martha Hanum Basyaroh; Tri Ananda Mei Saputri; Nur Laeli Maghfiro; Isna Nurjanah; Dea Feby Septiani; Eva Nurul Anisa (The Community Engagement Journal, 2021)
In this report, Walisongo Semarang UIN students majoring in Islamic Accounting, Faculty of Economics and Islamic Business, have participated in Tax Volunteer activities by practicing the task of assisting taxpayers in submitting Annual Tax Returns by using e-Filing at Pratama Jepara’s Tax Office. This task is a Tax Volunteer activity organized by the Central Java I Regional Tax Office in collaboration with Tax Centers throughout Indonesia, one of which is the Walisongo Tax Center in support of receiving Annual Tax Returns in 2020 and increasing taxpayer compliance. There are 20 students who have followed an internship at Pratama Jepara’s Tax Office with an annual SPT reporting service for Individual Taxpayers. The assignment of 20 students as Tax Volunteers has been going on for 1.5 months and the activity starts from February-March. As a result of this activities, students have been able to provide assistance in filling Personal Taxpayer's Tax Return with E-Filing and assisting Taxpayer services.